2017
DOI: 10.17371/uhd2017.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Hemşi̇releri̇n Afetlere İli̇şki̇n Görüşleri̇ Deneyi̇mleri̇ Ve Hazirlik Algisi

Abstract: Öz: Amaç: Araştırma, bir kamu üniversitesi hastanesinde ça-lışan hemşirelerin afetlere ilişkin görüşlerini, deneyimlerini, eğitim gereksinimlerini ve afetlere hazır olma algılarını belirlemek amacıyla tanımlayıcı tasarımda gerçekleştirilmiştir. Yöntem: Araştırmanın evrenini toplam 1236 hemşire oluştu-rurken, örneklemini gönüllü olarak araştırmaya katılmayı kabul eden 406 hemşire oluşturmuştur. Araştırma verilerinin toplanmasında; 13 soruluk anket formu ve afetlere hazır oluşluk algı durum ifadesinden yararlanı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…In this regard, 99.4% of the nurses included in our study defined the concept of disaster as natural disasters such as earthquakes and landslides. In a study conducted by Taşkıran and Baykal, it was determined that nurses evaluated all types of disasters as very probable or probable and especially they see the earthquakes which are seen more and more often very probable [31]. The results of this study and the results of our study are similar.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this regard, 99.4% of the nurses included in our study defined the concept of disaster as natural disasters such as earthquakes and landslides. In a study conducted by Taşkıran and Baykal, it was determined that nurses evaluated all types of disasters as very probable or probable and especially they see the earthquakes which are seen more and more often very probable [31]. The results of this study and the results of our study are similar.…”
Section: Discussionsupporting
confidence: 79%
“…In the study conducted by Şensoy and Nahcivan, 99.5% of the nurses stated that they believed that the role of nurses was after the disaster [30]. In the study conducted by Taşkıran and Baykal, 95.6% said that nurses had a role after the disaster [31]. In the study conducted by Basal and Ahmed, 58.5% of nurses stated that they have a role to provide care services in disasters [32].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of experience during a disaster response leads to stress and fear, but belief in the adequacy of one’s preparation for a disaster will increase student confidence (Kalanlar, 2018; Ma et al, 2021; Taşkiran & Baykal, 2017). Satoh et al (2018) found that students who took part in a disaster nursing education program had higher qualification levels than those still in the program and those who were not yet enrolled.…”
Section: Introductionmentioning
confidence: 99%
“…Disaster preparation is of vital importance for responding effectively to the immediate and long-term needs of affected communities (Taşkiran & Baykal, 2017). To be able to respond effectively, health teams need to have the necessary education and adequate qualifications.…”
mentioning
confidence: 99%
See 1 more Smart Citation